Acute exhaustive exercise under normoxic and normobaric hypoxic conditions differentially regulates angiogenic biomarkers in humans - Suhr, F.; Knuth, S.; Achtzehn, S.; Mester, J.; de Marees, M. (Medicina, 2021)
Background and Objectives: Angiogenesis describes the outgrowth of new capillaries from already existing ones. Different biomarkers regulate this process. Physical exercise and hypoxia are key stimuli for the activation of different angiogenic molecules, such as the vascular endothelial growth factor (VEGF). matrix metalloproteases (MMPs)-2 and -9 or the extracellular matrix cleavage fragment endostatin. The present study aimed to investigate influences of short-term, intensive cycling exercise under both normoxic and normobaric hypoxic conditions on the mentioned parameters. Materials and Methods: Twelve male subjects (age: 23.3 ± 2.0 years) participated in the study. All subjects conducted four intensive cycling tests until individual exhaustion in a randomized order under the following conditions: normoxia, 2000 m, 3000 m and 4000 m above sea level. Blood samples were taken before (pre) and 10 min, 30 min, 60 min and 240 min post exercise and were analyzed by ELISA. Results: VEGF showed a significantly reduced concentration compared to the pre-value solely under 4000 m at 10 min post exercise. MMP-2 showed significantly reduced concentrations at 240 min post exercise under 4000 m. MMP-9 increased at 240 min post exercise under both 2000 m and 4000 m conditions. Endostatin was significantly increased at 10 min post exercise independently of the applied stimulus. Conclusions: The presented data show that intensive short-term exercise bouts facilitate the bioavailability of angiogenic, ECM (extracellular matrix)-related biomarkers. This finding is interesting for both health- and performance-related research as it demonstrates the positive effects of intensive short exercise interventions.